Effectiveness of Electronic Ticketing Implementation in the District Banyumas - Kusuma, Darmawan (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to determine the effectiveness of the implementation of Electronic Tickets in Banyumas Regency and the shortcomings of the use of Electronic Tickets in Banyumas Regency itself. The approach method in this research is to use a normative - empirical approach. The data used are primary and secondary data. This data is analyzed qualitatively using descriptive analysis method. The increase in the number of motorized vehicles has resulted in rampant traffic violations such as running red lights, not using helmets, and going against the flow. As a result, traffic on the road becomes chaotic and causes congestion. Electronic ticketing is one of the programs implemented by the government based on Article 272 Paragraph 1 of Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation to facilitate the monitoring of traffic violators on public roads in Banyumas Regency The obstacles in its implementation internally are inadequate facilities and uneven distribution on each road and externally this program is still difficult to understand by some people, especially for people who are less familiar with technology.